Anodic Oxidation as a Means to Produce Memristive Films. Issue 3 (July 2016) - Diamanti, Maria Vittoria; Pisoni, Riccardo; Cologni, Andrea; Brenna, Andrea; Corinto, Fernando; Pedeferri, MariaPia
Purpose: In the past few years there has been growing interest in memristive devices. These devices rely on thin metal oxide films with a peculiar structure and composition, making precise control of oxide features vital. To this end, anodic oxidation allows a very large range of oxides to be formed on the surface of valve metals, whose thickness, structure and functional properties depend on the process parameters introduced. This work reports how memristive anodic oxides were obtained on titanium and other valve metals, such as niobium and tantalum. Methods: Anodic oxidation was performed on valve metals by immersion in H2 SO4 or H3 PO4 electrolytes and application of voltages ranging from 10 to 90 V. The memristive behavior was evaluated by cyclic voltammetry. Results: The behavior of differently grown oxides was compared to identify the best conditions to achieve good memristive performances. High voltages were identified as not suitable due to the excessive oxide thickness, while below 20 V the film was not thick and uniform enough to give a good response. Surface preparation also played a major role in the observation of memristive properties. Conclusions: Optimal surface preparation and anodizing conditions were seen to give high memristive perfomances on both titanium and niobium oxides, while on tantalum oxides no reproducibility was achieved.